Synthesis, Identification and Preliminary Pharmacological Evaluation of New Hydrazone and 1, 3, 4-oxadiazole Derivatives of Ketorolac - AL-Hashemmi, Aliaa; Muthanna S. Farhan (Iraqi Journal of Pharmaceutical Sciences, 2024)
New series of hydrazones (3a–b) and 1, 3, 4-oxadiazole S-alkylated derivatives (5a–b) of ketorolac (NSAID) were synthesized and their structures were identified by using ATR-FT-IR and ¹HNMR spectroscopic analytical techniques. The synthesized compounds were evaluated in vitro for their antimicrobial activity against Gram-positive bacteria (Staphylococcus aureus), Gram-negative bacteria (Escherichia coli), and fungal species (Candida albicans). After the approval of the ethical committee in the college of pharmacy, University of Baghdad, In vivo screening for their anti-inflammatory activity was done using albino rats as an animal model that were subjected to white egg-induced acute inflammation. Results have shown that the target compounds were successfully synthesized, and it was discovered that they have mild to moderate activity against E.Coil and S.aureus while no effect has shown on C.albicans. In vivo studies showed they were effective in lowering paw edema thickness and had an anti-inflammatory effect similar to that of the standard (ketorolac)